Factors of food dimension affecting customer satisfation in family restaurants / Norshahniza Sahari, Nora Mohd Basir and Rohani Jangga - Sahari, Norshahniza; Moho Basir, Nora; Jangga, Rohani (2012)
This study aims to determine the principal drivers of customer satisfaction in the aspect of meal or food dimension (i.e. food quality, food pricing, food portioning, and food presentation) in family restaurants in Malaysia. Moreover, the study investigates the relationship between factors of food dimension and customer satisfaction in family restaurants. A total of 460 dine-in customers were randomly selected from 40 outlets of family restaurant chains in Malaysia and submitted feedback forms. The findings indicate that customer satisfaction is influenced most by the quality of food, followed by the presentation of food, meal portion and food pricing (in that order). Furthermore, results show that all factors of food dimension have a significant impact on family restaurants in Malaysia. Thus, this study provides potential ways for restaurateurs to increase customer satisfaction and loyalty by improving their understanding of the factors of food dimension that influence customer satisfaction.